The Eclectic Method of Teaching Arabic According to Mahmud Yunus: Its Application at the Darus Salam Islamic Boarding School, Gontor - Salam, Muhammad Yusuf; Asrori, Imam; Hamid, M. Abdul (ISTAWA, 2022)
This study aims to reveal: 1) Mahmud Yunus' thoughts on the application of the Eclectic Method to teaching Arabic language material, 2) the reflection of Mahmud Yunus' thoughts on the implementation of the Eclectic method of teaching Arabic material at the Darus Salam Gontor Islamic boarding school. This study used a qualitative design, with two approaches; 1) literature study on Mahmud Yunus's thoughts on the Eclectic Method and 2) case study on discussing the implementation of the Eclectic Method in Mahmud Yunus' perspective. The research data were obtained using documentation, observation, and in-depth interviews. The data is then validated for correctness, suitability and reliability through data triangulation. The findings of this study illustrate that; (1) according to Mahmud Yunus that each branch of the Arabic language material is taught with various methods while still centered on one method (direct method), (2) The implementation of Arabic teaching methods at Pondok Gontor Sembilan shows conformity with Mahmud Yunus's thoughts on aspects of combining methods which is in line with the direct method in a systematic and tiered manner.